DAMPAK PENERAPAN MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA PELAKU INDUSTRI TEH - Perdana, Tomy; -Sa’id, E. Gumbira; Ma’arif, Syamsul; Tasrif, Muhammad (Lampung University)
The tea industry participants have to deliver their products with a good quality, quantity, continuity, right time,and the lower price. The efficiency is not only applied to individual business entity, but also applied to all participants in the tea industry supply chain. Recently, business decisions in the tea industry supply chain network still have individually and uncoordinated. This condition is different from the ideal supply chain management concept. Each business participants coordinates directly and transparently in the collaborative decisions making which aims to satisfy consumers in high efficiency level. The aim of this research are (1) identify and modellingÂ the recent tea industry supply chain system; (2) analyze and simulate of the of supply chain management implementationÂ in the tea industry; and (3) recommend the supply chain management strategy which can improve the performance of all the participants involved in tea industry. The research is using the âSystem DynamicsâÂ which used as a system approach using computers to analize and solving the problem and focused to analize and policy design.Â The application of the supply chain management in the tea industry has a high ability to keep the level of inventory in optimum condition, then stockout was nothing happened. Inline with those condition, the application oh the supply chain management also avoids overstock which can cause high cost production. At the end, the supply chain management can improve the profitability of the involved participants on the tea industry supply chain.Â In the effort to improve the tea industry supply chain need a cooperative development on the smallholders plantation level.